2023
DOI: 10.3390/jcm12031115
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Thyroid Profile of Patients with Alopecia

Abstract: Thyroid hormones are required for the physiological growth and maintenance of hair follicles. We aim to study the thyroid profile of patients with alopecia. This is a narrative review. PubMed literature was searched from 2013 to 2022. We followed different types of alopecia: alopecia areata (AA), androgenic alopecia in males and females, telogen effluvium (TE), frontal fibrosing alopecia (FFA), lichen planopilaris, and alopecia neoplastica (AN). AA shares a common autoimmune background with autoimmune thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 118 publications
1
11
0
Order By: Relevance
“…On the other hand, regulatory T cells are involved in both AA and thyroid condition progression. In line with this, some studies demonstrate a higher likelihood of AA in patients suffering from autoimmune hyperthyroidism or hypothyroidism as compared with healthy controls [ 100 , 102 ].…”
Section: Thyroid Hormonesmentioning
confidence: 70%
See 2 more Smart Citations
“…On the other hand, regulatory T cells are involved in both AA and thyroid condition progression. In line with this, some studies demonstrate a higher likelihood of AA in patients suffering from autoimmune hyperthyroidism or hypothyroidism as compared with healthy controls [ 100 , 102 ].…”
Section: Thyroid Hormonesmentioning
confidence: 70%
“…For example, a study on 1232 men and women for 25 months identified 14.29% ( n = 176) of them with MPA. The prevalence of thyroid dysfunctions in the MPA subgroup differed with age as follows: 6.3% in patients below 20 years old, 17% in persons aged between 21 and 40 years, and 50% in individuals older than 40 years [ 102 ].…”
Section: Thyroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged telogen phase eventually results in excessive shedding of resting hair, resulting in the typical hair loss seen in TE. [18] Table 1 Summary of our result. 1 Showed that the hypothyroidism group had significantly higher mean SALT scores than both the euthyroid and hyperthyroidism groups (P < .001).…”
Section: Discussionmentioning
confidence: 92%
“…Alopecia (hair loss) due to endocrine disorders has always plagued humans ( 1 , 2 ). Animal models for studying hair follicles in humans are usually rats ( 3 ), mice ( 4 ), guinea pigs ( 5 ), rabbits ( 6 ), and dogs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%